The Performance of Teachers of Indigenous Pupils - Edaño, Domingo (JPAIR Multidisciplinary Research, 2019)
The study aimed to determine the factors affecting the teaching performance of school teachers handling indigenous students in public elementary schools in Botolan District, Division of Zambales, during S.Y 2017-2018. The study revealed that the teacher-respondents perceived “often” on psychological and educational factors while “sometimes” on sociological, supervisory assistance, and economics as factors affecting teaching performance. The teacher-respondents were rated “very satisfactory” in their teaching work performance. There are no significant differences in the perception towards psychological, sociological, educational, supervisory assistance, and economic as factors affecting teaching performance; and no relationship between the work performance and factors affecting work performance as psychological, sociological, educational, supervisory assistance, and economic factors, respectively. Teachers are encouraged to explore multiple intelligences in order to improve a variety of traits and abilities for better teaching and learning process; the school should foster more the harmonious relationship and create a healthy working environment; to revisit the curriculum for possible modifications in order to meet the varying levels of IP’s abilities; to conduct seminars on human relation for better understanding on social duties, interpersonal traits and relations with other people; and since there is no relationship between the teaching performance and the factors affecting the teaching performance; therefore, other studies along this line should be conducted using other variables.